Effect of Parents' Characteristics and Perceptions on Basic Immunization in Children at Dr. Zainoel Abidin Banda Aceh - Octavina Susanti; T.M. Thaib; Rusdi Andid; Sulaiman Yusuf; Anidar Anidar; Jufitriani Ismy; Darnifayanti Darnifayanti (Budapest International Research and Critics University, 2020)
Immunization is a form of health intervention that is effective in reducing infant and under-five mortality rates. In Indonesia Aceh is the province with the lowest immunization coverage, where only 20% of Acehnese children receive complete basic immunization. M e n g analysis of the influence of parents' characteristics and perceptions of primary immunization in children in the General Hospital Dr. Zainoel Abidin Banda Aceh. This type of research is descriptive analytic with approach cross sectional using a questionnaire as a research instrument to the parents of the patients in the wards and child polyclinic period from June to July 2020. A sample of 51 people with methods Consecutive sampling. Data analysis used Chi-square test and Fisher exact test. Based on the results of the analysis of the relationship between parental perceptions and completeness of basic immunization, the results were obtained ( p > 0.05 ), for the assessment of the relationship between parental characteristics in the form of age, monthly income level and number of children with completeness of basic immunization in children, the results were obtained ( p > 0.05). , while the characteristics of the level of parental education with completeness of basic immunization in children obtained hacil ( p <0.05). There is an influence of parental characteristics, namely the level of education with completeness of basic immunization in children, while other variables, namely parents' perceptions, parental age, monthly income and number of children in one family do not affect the completeness of basic immunization in children at Dr. Zainoel Abidin Banda Aceh.